Compensation temperatures and exchange bias in La1.5Ca0.5CoIrO6 - Coutrim, L.T. (2016)
We report on the study of magnetic properties of the La1.5Ca0.5CoIrO6 double perovskite. Via ac magnetic susceptibility we have observed evidence of weak ferromagnetism and reentrant spin glass behavior on an antiferromagnetic matrix. Regarding the magnetic behavior as a function of temperature, we have found that the material displays up to three inversions of its magnetization, depending on the appropriate choice of the applied magnetic field. At low temperature, the material exhibits exchange bias effect when it is cooled in the presence of a magnetic field. Also, our results indicate that this effect may be observed even when the system is cooled at zero field. Supported by other measurements and also by electronic structure calculations, we discuss the magnetic reversals and spontaneous exchange bias effect in terms of magnetic phase separation and magnetic frustration of Ir4+ ions located between the antiferromagnetically coupled Co ions.